2019
DOI: 10.1029/2019je005955
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Thermophysical Properties of Lunar Regolith at Low Temperatures

Abstract: The thermophysical properties of lunar regolith have been thoroughly investigated for temperatures higher than 100 K. For the near‐equatorial thermal measurements of the Apollo era, this temperature range was sufficient to generate appropriate models. However, recent measurements from the Lunar Reconnaissance Orbiter Diviner Lunar Radiometer Experiment have revealed polar temperatures as low as 20 K, with apparently lower thermal inertia than explainable by existing theory. In the absence of comprehensive labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 68 publications
(186 reference statements)
4
33
0
Order By: Relevance
“…This result confirms that the lunar regolith tends to slow down thermal conduction [13,16]. Such thermal insulation could be ascribed to the porous, pulverized, and granular attributes of the regolith, as investigated by the study [23]. Its improvement is the prediction of a lower thermal conductivity but a higher specific heat than previous research [9−13].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This result confirms that the lunar regolith tends to slow down thermal conduction [13,16]. Such thermal insulation could be ascribed to the porous, pulverized, and granular attributes of the regolith, as investigated by the study [23]. Its improvement is the prediction of a lower thermal conductivity but a higher specific heat than previous research [9−13].…”
Section: Resultssupporting
confidence: 81%
“…This research found potential landing sites for future explorations but did not further study subsurface temperature variation. The recent studies [13,23] explored the lunar regolith thermophysical properties. They used a theoretical formula of the lunar orbital elements to estimate the solar hour angle and the incident solar flux for one lunar day.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term stability of each species depends on how the temperature varies diurnally with depth (12). Thermal modeling shows that temperatures are stable below ~ 0.2 m depth (13). The LCROSS impactor was estimated to have excavated material from 1-3 meters deep in the PSR (14), so the volatiles observed in the plume originated below the depth of thermal stability.…”
Section: Elemental Compositionmentioning
confidence: 99%
“…Other speculations of such correlation include the fact that the presence of water ice deposits changes the average physical properties of lunar regolith, e.g., thermal inertia, dielectric constant, which results in large TB variations at different depths. Simulation of TB with physical parameters of lunar regolith and accurate solar flux in PSRs is necessary to provide proof for such speculation; however, the difficulty in obtaining the thermophysical parameters of lunar regolith at extreme low temperature and unknown rock abundance, etc., would result in the uncertainties of results [40]. Whether the temperature resolution of MRM data is enough to detect the presence of ice deposits is also questionable.…”
Section: Tb In Psr With Plausible Ice Evidence and Other Psrsmentioning
confidence: 99%